Physical mechanisms of the influence of γ-ray surface treatment on the characteristics of close AuNi/n-n+-GaN Schottky contacts - Torkhov N. A. Nikolay Aleksandrovich; Gradoboev A. V. Aleksandr Vasilyevich; Budnaev V. Vadim; Ivonin I. V. Ivan Varfolomeevich; Novikov V. A. Vadim Aleksandrovich (2022, 2022)
Title screen